Once-a-Day Ceftriaxone–Amikacin Combination as Empiric Antibiotic Therapy to Enable Outpatient Management of Febrile Neutropenia in Children—16-Year Experience from a Single Institute - Kanvinde, Shailesh; Mulay, Atul; Deshpande, Anand; Deshmukh, Chetan; Patwardhan, Sampada (South Asian Journal of Cancer, 2022)
Background To enable outpatient department (OPD) management of febrile neutropenia (FN), we used once-a-day (OD) ceftriaxone–amikacin (CFT-AMK) as empiric antibiotic therapy. Our experience over 16-year period is presented.Methods This was a retrospective study conducted from January2002 to December2017. Inclusion criteria were <18 years of age, undergoing cancer chemotherapy, and having FN. Exclusion criteria were FN after palliative chemotherapy, bone marrow transplantation, or at diagnosis of malignancy. Empiric CFT-AMK was used in all, except those having respiratory distress, hypotension, altered sensorium, paralytic ileus, or clinical evidence of peritonitis. Admission criteria were age <1 year, acute myeloid leukemia (AML) chemotherapy, poor performance status, need for blood transfusions, convenience, insurance, or persistent fever >48 to 72 hours after CFT-AMK. Outcomes analyzed were response (defervescence within 48–72 hours), OPD management, antibiotic upgrade, and mortality. AML diagnosis, >7 days to absolute neutrophil count >0.5 × 109/L, poor performance status, and malignancy not in remission were considered high-risk FN criteria.Results CFT-AMK was given in 877/952 (92.2%) FN episodes. Seventy-six percent had hematolymphoid malignancies. Response, antibiotic upgrade, and mortality were seen in 85.7 and 65.5% (p < 0.0001), 15 and 45.5% (p < 0.0001), and 0 and 2% (p = 0.003) of low- and high-risk patients, respectively. Treatment was started in OPD in 52%, of which 21.6% required subsequent admission. Of those initially admitted, early discharge (hospital stay < 5 days) was possible in 24.6%. Forty-one percent episodes were managed entirely on OPD. Overall, 80% of low-risk and 42% of high-risk episodes received treatment wholly or partially on OPD.Conclusion Our results show empiric OD CFT-AMK allows OPD management for most of the low-risk and a proportion of high-risk FN following chemotherapy in children, without compromising clinical outcomes.
Keywords: febrile neutropenia; outpatient management; ceftriaxone–amikacin